CALCIUM OXIDE CHARACTERISTICS PREPARED FROM AMBUNTEN’S CALCINED LIMESTONE - Fatimatul Munawaroh; Laila Khamsatul Muharrami; Triwikantoro Triwikantoro; Zaenal Arifin (JURNAL PENA SAINS, 2018)
Calcium oxide (CaO) and calcium carbonate (CaCO3) are widely used in industry. CaO and CaCO3 can be synthesized or derived from limestone. The purpose of this study to determine the characteristics of CaO calcined limestone from Ambunten Sumenep. Lime in calcined at 850 ° C for 6 hours. Characterization of X-ray fluorescence (XRF) was conducted to determine the chemical composition of limestone, X-ray diffraction test (XRD) to find the lime crystalline phase and FTIR test to determine the absorption of wave number. XRF test results showed that the limestone chemical composition consisted of Ca of 95.37% as the dominant element, Mg of 4.1%, Fe 0.17% and Y by 0.39%. The XRD test results showed that the limestone crystal phase is ankerite (Ca [Fe, Mg] [CO3] 2) and after the calcined phase calcination is vaterite (Ca [OH] 2), calcite (CaO) and calcite (CaCO3). While the FTIR test results show that the CaO spectra are seen at 3741.24, 1417.12 and 874.14 cm-1.